Prevalence and characterization of Burkholderia gladioli in Iran, from bacterial dry rot of saffron corms (Crocus sativus L.) - KARIMI-SHAHRI, Mahmoud-Reza; ZAKIAGHL, Mohammad (Phytopathologia Mediterranea, 2024)
Iran is the main world producer of saffron (Crocus sativus L.), but a bacterial disease continues to threaten saffron production, causing severe flower failure, rot on flowering tubes, delayed vegetative growth, premature yellowing of leaves, bare patches in saffron farms, reddish-brown lesions in the germination zones of roots, and rot of saffron corms. Field surveys in Razavi-Khorasan and Southern-Khorasan provinces revealed high incidence of Burkholderia gladioli dry rot symptoms in saffron farms, with symptoms observed during flowering on leaves and corms. Twenty-four bacterial isolates from symptomatic saffron corms from different parts of Iran were characterized. These bacteria were identified as Burkholderia gladioli, based using phenotypic characteristics, species-specific PCR, and sequencing analyses of the 16S rRNA and 16S-23S intergenic transcribed spacer regions. All 24 isolates triggered hypersensitive reactions in tobacco and pelargonium leaves, although pathogenicity tests showed that only 21 isolates were capable of causing rots on saffron corms.